MENSTIMULASI KECERDASAN EMOTIONAL ANAK SEJAK USIA DINI - HAYATI, NUR (FOUNDASIA, 2008)
The success of people in their life is influenced by various factors. According to the research of some psychologists, the intellectual intelligence factor has only little influences to the life success, while the rest influenced by emotional intelligence factor and other support factors. Emotional intelligence will not appear just like that, however, it needs to be growth and trained as early as possible. Early age children have capability to grow their emotional intelligence although it still conforms to their egocentric dominated development. That gold potentiality witl develop very well when it is often stimulated and sharpened. It is realized that an early age child who has emotional intelligence will be more adaptable to his/her environment and be more competent to cope with his/her lift problem. The life success of people will be easier to be attained if he%she has emotional and intellectual intelligence. To grow children emotional intelligence, there are some areas that need to he developed those are introducing self-emotion, managing emotion, self motivating, knowing other emotion or empathy and building relationship. To actualize those five areas is a genius first step in stimulated children emotional intelligence skill. The parents can actualizefilve areas emotional intelligence with develop love gjfirur, how to teach altitude, how to develop empathy, hew to teach honesty and realistic thinking.